ANALISIS PELAKSANAAN PENGELOLAAN PEMUNGUTAN, PENYETORAN, DAN PELAPORAN PPN DAN PPh PASAL 22 WAJIB PUNGUT BUMN PADA PERUM PERUMNAS KANTOR PUSAT - Gatot Hery Djatmika; Putu Tirta Sari Ningsih; Erent Dany Pratama; Yohanes Bowo Widodo (Pusat Riset dan Inovasi Nasional, 2021)
This study aims to determine the process of applying collection, depositing, reporting value added tax and income tax article 22 compulsory collection, and tax compliance Perum Perumnas. In this study the dependent variable used is PMK-136 /PMK.03 / 2012, PMK-37 / PMK.03 / 2015, and UU KUP No. 16 of 2009, while the independent variable in this study is the Obligatory Value Added Tax Collection, Article 22 Income Tax and Tax Compliance. This study uses descriptive qualitative research methods and the data used in the form of secondary data is a report on the Period of Value Added Tax Collection and Notification of Income Tax Article 22 during January to December 2018. The population in this study is Perumnas Corporation engaged in real estate owned by a State-Owned Enterprise. And using information from 3 people from Perum Perumnas to dig up information and data related to taxation at Perum Perumnas, using unstructured interviews, documentation, and literature studies. Data analysis techniques begin by revealing events or facts, circumstances, phenomena, variables and circumstances that occur when the study takes place by presenting what actuallyhappened. The results of this study indicate that in general the process of applying collection, depositing, reporting on Value Added Tax and Income Tax Article 22 Mandatory Collection is in accordance with PMK-136 / PMK.03 / 2012 and PMK-37 / PMK.03 / 2015, and can it was concluded that Perum Perumnas was obedient in carrying out its tax obligations in accordance with the general tax provisions Law No. 16 of 2009.